The complex approach of Gamification Strategies in Higher Education - Peñafiel Rodriguez, Wilma Nelly (2021)
The objective is to present a theoretical summary of gamification strategies in Higher Education and its relationship with complex thinking. The methodology used is a documentary bibliographic review that comprised four phases: Approach of the research questions, search for information. Information organization and information selection criteria, based on a review of the literature in Scielo, Doaj, Latindex, Redalyc and Google Academic. It delves into game-based learning, serious games, and gamification. The importance of the game in the learning process and the impact of the application of gamification in teaching are studied. Finally, an analysis of the literature on gamification is carried out, complex principles, its relationship with gamification and characteristics of complexity.